Modelo de negócio orientado à sustentabilidade: diretrizes para vinícolas que produzem produtos orgânicos - Cardoso, Jeferson Jonas (Universidade do Vale do Rio dos Sinos, 2021)
Given the evolution of environmental degradation and the uneven and heterogeneous formation of global society, agendas related to sustainable development have been highlighted in academic and corporate discussions. Thus, the demand to meet the needs of the current generation without compromising the ability of future generations to meet their own needs has reinforced the urgency of changes in the way companies do business. Therefore, the value created and delivered by a company must not only be of interest to the customer, but also be beneficial to the environment and society. And in this scenario, the production of organic, natural, and biodynamic wines has proven to be a way of generating economic, environmental, and social value, since organic agriculture seeks to promote health through production without environmental impacts. In this view, this work aims to propose a set of guidelines that guide the increase of sustainability in the business model of organic wineries. For this purpose, a multiple case study was used, of exploratory character and qualitative approach. A theoretical framework was developed to explain the core elements of a sustainable business model, and the business model of 8 wineries producing organic grape-based beverages was empirically explored. The main results of the research pointed out that most organic wineries still perceive sustainability as a concept focused only on the environmental aspect, thus neglecting the social. This orientation promotes practices that seek to mitigate environmental impacts on the properties while initiatives to generate social value are not perceived. And in order to collaborate with this need, a set of guidelines was developed that seek to guide the increase of sustainability in these business models.
Keywords: Modelo de negócio orientado à sustentabilidade; Sustentabilidade; Modelo de negócio; Vinícolas; Sustainable business model; Sustainability; Business model; Wineries; ACCNPQ::Engenharias::Engenharia de Produção